On I-lacunary Summability Methods of Order a in Intuitionistic Fuzzy n-normed Spaces - Savaş, E. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we introduce and study the notion I-statistical convergence of order α, and I-lacunary statistical convergence of order a with respect to the intuitionistic fuzzy n-normed space and also we investigate their relationship and some inclusion theorems are roved.